2021
DOI: 10.4149/neo_2020_191023n1080
|View full text |Cite
|
Sign up to set email alerts
|

Association of triple positivity with prognostic parameters and overall survival in a population-based study of 6,122 HER2-positive breast cancer patients: analysis of real-world clinical practice based on a research database

Abstract: Triple-positive breast cancer (TPBC), i.e. HER2-positive (HER2+) and hormone receptors-positive breast cancer, is a specific subgroup of breast cancers. TPBC biology is characterized by strong mutual interactions between signaling pathways stimulated by estrogens and HER2 amplification. The present study aims to carry out a population-based analysis of treatment outcomes in a cohort of hormone receptor (HR) positive and negative breast cancer patients who were treated with anti-HER2 therapy in the Czech Republ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…However, the results pertaining to HER2+ status were not entirely consistent. Previous studies [18][19][20][21][22] have reported a similar association between ER+ and PR+ status and improved OS, DSS, and progression-free survival, for both male and lactating breast cancer. Tis aligns with our fndings, although we did not observe any correlation between ER−/PR+ status and clinical outcomes in BC-LuC due to the limited sample size.…”
Section: Discussionsupporting
confidence: 52%
“…However, the results pertaining to HER2+ status were not entirely consistent. Previous studies [18][19][20][21][22] have reported a similar association between ER+ and PR+ status and improved OS, DSS, and progression-free survival, for both male and lactating breast cancer. Tis aligns with our fndings, although we did not observe any correlation between ER−/PR+ status and clinical outcomes in BC-LuC due to the limited sample size.…”
Section: Discussionsupporting
confidence: 52%
“…The higher incidence of nodes involvement and local advanced stage could be partially related to the screening suspension and delayed diagnosis (6). Additionally, we observed a different distribution of cancer grades, which could also be partially correlated with lymph nodes advanced stages (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). Nonetheless, at multivariate analysis, waiting time on list, significantly longer during the Lockdown, seems to be the only predictive factor of lymph nodes involvement progression.…”
Section: Discussionmentioning
confidence: 72%
“…Out of 6,122 patients who met the above-mentioned criteria, a total of 4,532 patients were included in the analysis after balancing the data by propensity score matching (R statistical software with MatchIt package) with respect to age (p=0.335 after matching) and grade (p=0.998 after matching). The propensity score matching analysis followed the population analysis in a previous manuscript by the same authors focused on comparison of patients' groups according to their ER and/or PR receptor status in the real-world settings (10). Classified according to their ER and/or PR receptor status, the two resulting groups contained approximately the same numbers of patients, patients with both ER-and PR-negative (n=2,268) and patients with either ER or PR positive (n=2,264 Statistical analysis.…”
Section: Methodsmentioning
confidence: 99%